Two functional alpha-tubulin genes of the yeast Saccharomyces cerevisiae encode divergent proteins. - Schatz, P J (1986)
Two alpha-tubulin genes from the budding yeast Saccharomyces cerevisiae were identified and cloned by cross-species DNA homology. Nucleotide sequencing studies revealed that the two genes, named TUB1 and TUB3, encoded gene products of 447 and 445 amino acids, respectively, that are highly homologous to alpha-tubulins from other species. Comparison of the sequences of the two genes revealed a 19% divergence between the nucleotide sequences and a 10% divergence between the amino acid sequences. Each gene had a single intervening sequence, located at an identical position in codon 9. Cell fractionation studies showed that both gene products were present in yeast microtubules. These two genes, along with the TUB2 beta-tubulin gene, probably encode the entire complement of tubulin in budding yeast cells.